Systematic Exploration of Countertransference Phenomena in the Treatment of Patients at Risk for Suicide. Issue 1 (2nd January 2020) - Soulié, Tess; Bell, Elliot; Jenkin, Gabrielle; Sim, Dalice; Collings, Sunny
Abstract : Despite its critical role in clinical suicidology, empirical evidence on the nature of countertransference (CT) to patients at risk for suicide (PRS) is lacking. This study aimed to provide a systematic description of CT phenomena to PRS. Psychiatrists, psychologists, and psychotherapists completed the Therapist Response Questionnaire (TRQ) online, with reference to a PRS. Factor analysis (n = 267) yielded a 7-factor structure, including 1) entrapped/rejecting, 2) fulfilled/engaging, 3) aroused/reacting, 4) informal/boundary crossing, 5) protective/overinvolvement, 6) ambivalent/inconsistent, and 7) mistreated/controlling. On average, clinicians reported that CT dimensions tended to not apply to them, except for the positively connoted factor. Our findings suggest that patients at risk for suicide elicit specific dimensions of CT. We offer two alternative interpretations of clinicians' CT endorsement patterns.